Genome-Wide Analysis of CPP Transcription Factor Family in Endangered Plant Phoebe bournei and Its Response to Adversity - Ronglin Liu; Yizhuo Feng; Qingyan Li; Hua Wu; Shengzhou Guo; Junnan Li; Xiaomin Liu; Yanlin Zhang; Xinghao Tang; Shijiang Cao (Plants)
The CPP gene family comprises transcription factor genes containing a conserved CRC domain, which is mainly involved in plant development and evolution. Although CPP genes have been widely studied in many plants, little is known about them in woody plants, especially in the endangered species Phoebe bournei (Hemsl.). In the genome of Phoebe bournei, we identified 11 PbCPP genes (PbCPP1-PbCPP11) distributed on four chromosomes, with large differences in the number of amino acids. They encode both acidic and alkaline proteins. A phylogenetic analysis showed that these PbCPP genes can be divided into three subfamilies, A, B, and C, which contain seven, two, and two genes, respectively. Through an interspecific collinearity analysis, we identified homologous PbCPP genes. A promoter cis-acting element analysis revealed that PbCPPs contain a variety of elements that respond to plant hormones, stress signals, and light and play a role in growth and development, and most PbCPP genes (except PbCPP3 and PbCPP8) contain MYB binding site elements that regulate drought-induced stress responses, indicating that they play an important role in plant drought resistance. An expression analysis showed that PbCPP3 and PbCPP4 expression was high in the roots and stems and lower in the leaves, whereas the expression of most of the other genes was low in the roots, stems, and leaves. In addition, six representative PbCPP genes were detected using qRT-PCR. The results show significant differences in the expression of PbCPP genes under abiotic stress conditions (drought, cold, and salt), indicating that they play an important role in stress responses. This study preliminarily verified the role of the PbCPP gene family in different abiotic stress responses, which is of great significance for understanding its mechanism in plant growth and development and stress adaptation.